Evaluation of in-house loop-mediated isothermal amplification for tuberculosis diagnosis compared with Xpert MTB/RIF - Habeenzu, Charity; Nakajima, Chie; Solo, Eddie; Bwalya, Precious; Kajino, Kiichi; Miller, Mari; Kurosawa, Youichi; Mudenda, Victor; Kasonka, Lackson; Suzuki, Yasuhiko; Matsuba, Takashi (The Journal of Infection in Developing Countries, 2017)
Introduction: To evaluate the diagnostic performances of an in-house loop-mediated isothermal amplification (LAMP) kit and the Xpert MTB/RIF test for the diagnosis of pulmonary tuberculosis in a resource-limited setting, this study was performed at the University Teaching Hospital, Ministry of Health, the Republic of Zambia. Methodology: Two hundred sputum specimens obtained from new tuberculosis (TB) suspects were used for the evaluation of the diagnostic performance of an in-house LAMP kit in comparison with the Xpert MTB/RIF kit. Results: The sensitivity of in-house LAMP and Xpert MTB/RIF was 96.9% and 95.4% in smear-positive samples, 96.8% and 100% in smear-positive/culture-positive samples, and 39.1% and 73.9% in smear-negative/culture-positive samples, respectively. The specificity of in-house LAMP and MTB/RIF kits with culture was 96.5% and 94.5%, respectively. This indicated the superiority of the Xpert MTB/RIF kit; however, mechanical errors during sample processing and the insufficient quantity of samples by Xpert MTB/RIF kit occurred at 2.0% and 19.7%, respectively, comparing to the 100% accessibility of in-house LAMP. Conclusions: Considering the results obtained in this study together with the easy setup with much simpler equipment, such as an aluminum heat block or water bath, in in-house LAMP compared with real-time polymerase chain reaction equipment in Xpert MTB/RIF kit, the applicability of in-house LAMP for the screening of tuberculosis directly from sputum in resource-limited setting seemed to be high.